Property tax, taxpayers voices and tax compliance in local governments: A case study of land use charge in Lagos State, Nigeria - Augustine, Adekoya A; Ifayemi M, Olayinka (International Journal of Emerging Trends in Social Sciences, 2023)
Property Tax (PT) is chargeable on real property on an annual basis. Worldwide, PT has been a subject of political debate as it plays a vital role in the area of political, social and economic activities. Property taxes evasion are very high in developing countries and perceived to have adversely affects Local Government (LG) revenues. Many studies have been conducted on taxpayers’ compliance behaviour, but not many focused on PT, taxpayer voices and Tax Compliance (TC). This study examined PT, taxpayers’ voices and TC in LGs using Land Use Charge (LUC) in Lagos State, Nigeria as case study. The study employed explanatory research design. Secondary data on LUC collections shared to LGs from 2011-2021 were used. Descriptive statistics of data analysis was adopted. The study revealed that the power of citizens’ voices against government policies and unfriendly laws has negative impact on tax revenues and compliance, this leads to citizens’ apathy, non-compliance and loss of tax revenues. The study also revealed that there are less TC to PT due to few numbers of properties enumerated and taxpayers’ compliance rate. The study recommends that PT laws should be friendly, just and fair while a good PT administration with the use of modern technology of Geographic Information Systems mapping for property identification and tax collections be enhanced. Government should also promote public awareness on PT payment while LG legitimacy and accountability to taxpayers would enhance climate of trust, minimized fraud, eradicate corruption and ensure voluntary tax compliance.